Cell mediated immune response in human antirabies revaccination - Débora Regina Veiga; Carlos Roberto Zanetti; Nelson Figueiredo Mendes; Octávio Augusto de Carvalho Pereira (Revista do Instituto de Medicina Tropical de São Paulo, 1987)
The occurrence of secondary cell mediated immune response (CMI) in human antirabies immunization was studied. The Puenzalida & Palácios vaccine was used because it is routinely used in Brazil. CMI was evaluated by lymphoblastic transformation indices obtained in whole blood culture in the presence of rabies and control (nervous tissue) antigens. Eleven volunteers submitted to revaccination constituted the group under study, while three other volunteers submitted primo vaccination were utilized as control group. A clear secondary CMI to rabies antigen was detected in all the revaccinated volunteers who showed earlier and more intense response than the control group. Response to the control antigen, however, present in all the components of the first group was not detectable in two out of the three primovaccinated and very low in the third one.